Zygoparity in characidae-the first case of internal fertilization in the teleost cohort otomorpha - Fukakusa, Clayton Kunio; Mazzoni, Talita Sarah [UNESP]; Malabarba, Luiz Roberto (FapUNIFESP (SciELO), 2020)
Most teleosts are externally fertilizing, with internal fertilization occurring as a relatively rare event. Until now, Euteleosteomorpha is the only teleost cohort known to undergo internal fertilization. In the teleost cohort Otomorpha, it has been recorded the presence of sperm in the ovaries of some species of Characiformes and Siluriformes, but no fertilized eggs have been found so far in the female reproductive tract. It has been presumed that oocytes can be released into the water with associated spermatozoa and only there becomes fertilized, and the term insemination has been used to characterize the strategy adopted by these fish. Here, we present the discovery of the first case of internal fertilization in the teleost cohort Otomorpha, in Compsura heterura (Characiformes: Characidae). In the course of spawning, the eggs form the perivitelline space and the animal and vegetative poles within the ovaries, evidencing oocyte fertilization. The newly spawned eggs then continue to form the animal and vegetative poles and increase the perivitelline space. These eggs are in the zygotic stage. These data indicate that fertilized eggs are only retained for a short period, providing evidence that C. heterura is a zygoparous fish.
Keywords: Characiformes; Insemination; Ostariophysi; Reproduction; Spawning